Conditional cash transfers, schoolingand child labor: micro-simulating bolsa escola - François Bourguignon; Francisco H. G. Ferreira; Phillippe G. Leite (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2003)
Cash transfers targeted to poor people, but conditional on some behavior on their part, such as school attendance or regular visits to health care facilities, are being adopted in a growing number of developing countries. Even where ex-post impact evaluations have been conducted, a number of policy-relevant counterfactual questions have remained unanswered. These are questions about the potential impact of changes in program design, such as benefit levels or the choice of the means-test, on both the current welfare and the behavioral response of household members. This paper proposes a method to simulate the effects of those alternative program designs on welfare and behavior, based on microeconometrically estimated models of household behavior. In an application to Brazil's recently introduced federal Bolsa Escola program, we find a surprisingly strong effect of the conditionality on school attendance, but a muted impact of the transfers on the reduction of current poverty and inequality levels.
Keywords: 330; Conditional Transfers; Demand for Schooling; Child Labor JEL Codes: I38; J13; J22; J24; Öffentliche Sozialleistungen; Bildungsverhalten; Kinderarbeit; Armut; Brasilien